Discrimination Thresholds for Passive Tactile Volume Perception by Fingertips. (December 2019) - Zhang, Jian; Zhang, Zhilin; Go, Ritsu; Li, Chunlin; Wu, Jinglong
Haptic object perception is still poorly understood up to now. This study investigated the ability of human fingers to discriminate the volume of objects by passive touch. Experiments measured the discrimination threshold of volume using three tasks: passive tactile volume perception, passive tactile area perception, and active tactile volume perception. In each trial, we utilized two plastic cubes to successively stimulate the fingers, and participants were instructed to make comparisons between the stimulus objects' volume and area. Results showed that there was no significant difference in the discrimination thresholds of tactile volume perception between passive touch and active touch, whereas significant differences in the discrimination thresholds between fingertips, such as the thumb versus the pinky finger. In passive touch, the discrimination thresholds of volume perception were larger than that with surface area perception. We found that the discrimination of the volume of objects is more difficult than the discrimination of the area of the objects.